The brain that learns: an experience withreading practices in the early years of schooling (Research, Society and Development, 2019)
The aim of the present article is to present the results of a research that aimed to verify if projects to encourage reading in the daily school life can contribute significantly to the performance of students in the first years of schooling. The research conducted is a case study. The sample consisted of 16 students from a fifth grade class from Elementary School I of a public school. The data collection was carried out in the year 2017, being carried out the tests of the Diagnostic Evaluation of the Projeto Evalu-BH and observations of reading practices in the classroom. The encouragement of reading practices contributed significantly to the cognitive development of students not only in Portuguese but also in science and mathematics. Therefore, in order for teaching to promote important meanings for the cognitive development of students, it is suggested that teachers and managers of the Initial Years invest in reading practices allied to pedagogical action in the school context.